A Re-Engineering Approach To JPLâ€™s Galileo S-Band Project: Cost Estimation Assessment Using TQM - Becerra, Carlos E; Mahmood, Mo Adam; Trumbly, James E; Lackey, Charley (The International Journal of Accounting and Business Society, 1994)
The Jet Propulsion Laboratory (JPL) has, recently, been seriously concerned with costing new major projects. One of these projects is the Galileo S-Band project for which the National Aeronautic Space Administration (NASA) wants to enhance the data resolution capabilities while boosting data rates at an overall budgeted cap of $28.2 million. Addressed in this article are the problems relating to cost estimating, that JPL is facing as it makes the transition from a public organization towards a more semi- private organization. The current budget constraint at JPL coupled with recent economic, public, and political changes had forced government sponsored projects to adhere to a ï¬xed cost project environment. Present project costing techniques at the Jet Propulsion Laboratory consist of preparing project reliability and feasibility cost estimate studies. If the studies reveal project acceptance, work package agreements (WPA) are prepared, validated, and signed by the projects â€œin-chargeâ€ managers. These WPAs are, basically, contracts stating the requirements, the work force, person-hours, needed procurement, time frame, allocated budget, and expected deliverable for each of the projectâ€™s task operations. This seems to be the secure of JPLâ€™s current concerns. The feasibility and reliability project studies are based on past, similar, project experience submitted by middle management. Such an application of costing technique appears to work well from managementâ€™s point of view. After all, the cost estimates given by each process operation manager must be assumed to be reliable since they have had previous experience with similar, comparable projects. A new project costing estimation technique should be applied: A re-engineering tool approach driven by Total Quality Management (TQM) axioms. By allowing the actual engineer/programer to express their opinions a reï¬ne project cost estimate could be procured. An additional advantage to gaining a better project estimate is that JPL will also proï¬t from a more enthusiastic employee by knowing they have participated in not just working for the project but also having a stake in the initial requirement and budgeting stages. Accountability and performance measures are easier to implement as they are setting the boundaries by which they will be measured and held accountable.